2013
DOI: 10.1038/eye.2013.264
|View full text |Cite
|
Sign up to set email alerts
|

The psychological well-being and appearance concerns of patients presenting with ptosis

Abstract: Purpose Ptosis affects both the function and appearance of the eyes and face, because of drooping of the eyelids. Previous research has focused on functional impairment; however, similar appearance altering eye conditions have been demonstrated to have major impacts on psychosocial functioning. Methods This study examines the psychological well-being and appearance concerns of patients presenting with ptosis recruited from Bristol Eye Hospital using validated questionnaires focusing on demographics and psychos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…Previous research into the impact of ptosis and other conditions affecting the 69 appearance of the eyes(13) (14) (15) demonstrates negative impacts of these 70 conditions due to the psychosocial effects of living with an appearance altering 71 condition, and suggests that patients with ptosis may be motivated to seek surgery to 72 ameliorate the psychological impacts as well the functional concomitants of the 73 condition(15) (13). The withholding of ptosis surgery on the grounds that it is a 74 cosmetic procedure and is therefore unworthy of funding risks denying treatment to 75 patients experiencing significant reductions in quality of life (QOL) as the result of the 76 condition.…”
mentioning
confidence: 99%
“…Previous research into the impact of ptosis and other conditions affecting the 69 appearance of the eyes(13) (14) (15) demonstrates negative impacts of these 70 conditions due to the psychosocial effects of living with an appearance altering 71 condition, and suggests that patients with ptosis may be motivated to seek surgery to 72 ameliorate the psychological impacts as well the functional concomitants of the 73 condition(15) (13). The withholding of ptosis surgery on the grounds that it is a 74 cosmetic procedure and is therefore unworthy of funding risks denying treatment to 75 patients experiencing significant reductions in quality of life (QOL) as the result of the 76 condition.…”
mentioning
confidence: 99%
“…Moderate to severe blepharoptosis can impair visual function (e.g., loss of superior visual fields) [6] cause psychological distress (e.g., anxiety and depression) [5], reduce health-related quality of life [18], and cause tension-related headaches [7][8][9]. Blepharoptosis in older adults may be underestimated or ignored because both physicians and patients consider the condition to be a result of the aging process.…”
Section: Discussionmentioning
confidence: 99%
“…Richards et al reported that patients with blepharoptosis had higher levels of anxiety, depression, and concerns regarding their appearance than the general population [5]. When questioned about their visual function-related quality of life, BriceΓ±o et al reported that after surgery for ptosis repair, patients reported a significant increase in visual function [6].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, interventions that improve relationships, support systems, and family functioning may reduce the negative impact of stressors 9. Richards et al suggested that psychosocial factors and demographics were predictors of the development of appearance-related distress and compromised the psychological well-being of patients with ptosis 10. Therefore, appearance is an important aspect of health anxiety.…”
Section: Introductionmentioning
confidence: 99%